Brill's companion to the reception of Euripides - Lauriola, Rosanna.; Dēmētriou, Kyriakos N. (Brill's Companions to Classical Reception, 2015)
Brill's Companion to the Reception of Euripides provides a comprehensive account of the influence and appropriation of all extant Euripidean plays since their inception: from antiquity to modernity, across cultures and civilizations, from multiple perspectives and within a broad range of human experience and cultural trends, namely literature, intellectual history, visual arts, music, opera and dance, stage and cinematography. A concerted work by an international team of specialists in the field, the volume is addressed to a wide and multidisciplinary readership of classical reception studies, from experts to non-experts. Contributors engage in a vividly and lively interactive dialogue with the Ancient and the Modern which, while illuminating aspects of ancient drama and highlighting their ever-lasting relevance, offers a thoughtful and layered guide of the human condition.